HABITUAL ACTION DALAM KEPEMIMPINAN SPIRITUAL - Basit, Abdul (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2013)
Toward leadership crisis that crashed the nation of Indonesia, one of thefactors contributors come from universities, concerning Higher Education is anursery area of society and the national leaders. To overcome the crisis, it needed torepair the leadership models that are able to change and improve social and nationallife. The mandate of the university is shaping and sharpening thinking of thelecturers, students, and alumni to always siding, thinking and acting for the benefitand improvement of the surrounding communities. One alternative models ofleadership that are relevant to college is spiritual leadership.Spiritual leadership has been tested and researched by Louis W. Fry ( 2003)along with the comrades in the context of different organizations and the resultsshow the possibility of the application of this theoretical model for various types oforganizations. According to Fry spiritual leadership is the incorporation of thenecessary values, attitudes and behaviors to motivate intrinsically oneselves andothers to be such a way so that they have a sense of spiritual defense through the callof duty and membership.Spiritual leadership model is studied by the author in STAIN Purwokerto, asIslamic educational institutions which incidentally has been practicing spiritualvalues in their environment. The study was conducted using qualitative research andcase study approach.Spiritual leadership in STAIN Purwokerto is constructed based on threeimportant things: First, the existence of spiritual values that were held by leaders andserve as an ideology or belief to motivate himself and others. Spiritual values arevalues such are togetherness, belief or determination, and obeying the rules. Second,building tradition of spiritual leadership that is reflected in the actions taken byleaders in achieving the vision to be achieved by STAIN Purwokerto. The habitualprocess is done by sticking to spiritual values carried. Then it is implemented byissuing flagship programs supported by strategic policies carried out intensively sothat it becomes a regular agenda of the academic community and staff as well as toproduce a healthy organizational culture and quality. Third, organizational culture isfostered by building a dynamic atmosphere, full of family-like-feeling, cooperation,open and respectful in terms of spiritual, intellectual and professional. The efforts aremade from simple things and daily life by providing deep meaning so that it can beused as a driver towards the direction of progress .